Exposure to community violence and young adult crime: the effects of witnessing violence, traumatic victimization, and other stressful life events - Eitle, David James (Journal of research in crime and delinquency, 2002)
Evidence has accumulated that young people in America are witnesses to considerable violence at home and in the community. This study is the first to examine the association between witnessing community violence and criminal behavior in a representative sample of young adults. In addition, the authors consider whether receiving traumatic news, witnessing domestic violence, experiencing accidents, and being the direct victim of domestic and community-based violence are independently associated with young adult crime. The results indicate that recent exposure to violence in the community along with a history of receiving traumatic news, direct victimizations in the community, recent life events, and associations with criminal peers increase the risk for young adult criminal offending. The implications of these results are discussed